Text- und Data-Mining Die Anforderungen digitaler Forschungsmethoden an ein innovations- und wissenschaftsfreundliches Urheberrecht - Kleinkopf, Felicitas Lea (Schriftenreihe des Archivs für Urheber- und Medienrecht, 2022)
Digital methods such as text and data mining are utilised more and more frequently to gather knowledge, thereby offering the ability to recognise patterns in large data sets as well as being the basis of machine learning. This work examines this digital method from a copyright perspective, evaluating the significance and controlling effect of copyright barriers, the special interests involved in scientific copyright law and elements of interdisciplinary knowledge. This comprehensive analysis structures this complex legal matter, identifies deficits and suggests viable solutions. One focus lies on the long-term accessibility of the research data that are generated within this process.